IMPACT OF STRATEGIC PLANNING ON THE MANAGEMENT OF WATER UTILITY OPERATORS (OOA) IN MEXICO - Rodriguez-Rios, Rigoberto; Mayett-Moreno, Yésica (Seven Editora, 2026)
This study analyzes the impact of strategic planning on the management of Water Utilities (WU) in Mexico and its importance for improving operational and financial efficiency, as well as the sustainability of the service. Through the application of an instrument to 21 WU in the state of Sonora and other states, a significant association was identified between the size of the WU and the adoption of strategic tools (p<0.05). Thirty-three percent lack formal planning processes, and only 10% have a documented plan. WU management is primarily focused on short-term operations (43%) and sustaining daily operations (62%), with little emphasis on long-term projects (14%). A flexible planning model, adapted to the heterogeneity of the Mexican water context, is proposed to support decision-making and contribute to improving institutional performance with a focus on sustainable development. DOI: https://doi.org/10.56238/sevened2026.008-066